2013
DOI: 10.1016/j.taap.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and organophosphorus compounds

Abstract: Organophosphorous (OPs) pesticides are the most widely used pesticides in the agriculture and home. However, many acute or chronic poisoning reports about OPs have been published in the recent years. Mitochondria as a site of cellular oxygen consumption and energy production can be a target for OPs poisoning as a non-cholinergic mechanism of toxicity of OPs. In the present review, we have reviewed and criticized all the evidences about the mitochondrial dysfunctions as a mechanism of toxicity of OPs. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…1,28 Inhibition of AChE during both acute and chronic toxicity of these compounds plays a key role in the induction of disorders. For example, these factors lead to the development of hyperglycemic and hemostatic disorders related to glucose metabolism and can be regarded as …”
Section: Discussionmentioning
confidence: 99%
“…1,28 Inhibition of AChE during both acute and chronic toxicity of these compounds plays a key role in the induction of disorders. For example, these factors lead to the development of hyperglycemic and hemostatic disorders related to glucose metabolism and can be regarded as …”
Section: Discussionmentioning
confidence: 99%
“…As a primary site of cellular energy generation and oxygen consumption, mitochondrion is a likely target for OPs, which may explain their non-cholinergic toxicity (88,89). Recent research has focused on the possible roles of mitochondrial dysfunction in OP-induced toxicity through mitochondrial respiration rate, respiratory chain enzymes…”
Section: Possible Effects Of Ops On Hepatic Carbohydrate Lipid and mentioning
confidence: 99%
“…The best course of action to counter OP liver and mitochondrial toxicity in acute, subacute, sub-chronic, or chronic exposure is therefore to use antioxidants (89,119,165,166). The choice of antioxidants is wide, but several have been evidenced as potent against OP toxicity, including selenium (167), N-acetylcysteine (NAC), pentoxifylline (PTX), and alpha-tocopherol.…”
Section: Conclusion and Recommendations To Control Opinduced Liver Dmentioning
confidence: 99%
“…Some recent studies showed that sarin and other OP compounds induce multiple toxicities in vivo and in vitro (Banks and Lein, 2012;Karami-Mohajeri and Abdollahi et al, 2013). Treatment with OP compounds caused insult to neuronal cells and induced neuronal DNA damage, lipid peroxidation, mitochondrial dysfunction, and the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%